(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
Rainfall threshold estimation empirically to forecast rainfall-induced landslide events provides crucial information to reduce landslide impact. The landslide events triggered by rainfall are common in Cox’s Bazar district, especially during the monsoon season. Geological settings and climatic conditions make this area more landslide-prone leading to huge losses of lives and property. Establishing an effective early warning system based on a rainfall threshold value has become a top priority to save people’s lives, the economy, and the environment. We have employed three empirical approaches to estimate rainfall thresholds. Intensity-Duration, Event-Duration, and Antecedent Rainfall thresholds are the most conventional rainfall methods to identify the lowest amount of rainfall that triggers landslide. The Intensity-Duration (ID) and Event-Duration (ED) rainfall threshold equations are calculated using a simple power-law curve. For 5% exceedance probability level ID defined as: T5: I = 3.63 D-0.1313 & ED as T5: E = 3.63 D0.8687. Similarly, for 1% exceedance probability level ID defined as: T1: I= 2.78 D-0.1313 & T1: E = 2.78 D0.8687 for ED. Both 1% and 5% rainfall threshold equations are the minimum rainfall threshold equations. Since the 5% exceedance probability threshold line delineates the lower end of all the observed data points for landslide events, it is considered the minimum threshold line for Cox’s Bazar. According to the 5% exceedance probability level threshold equation, mean intensity of 2.39 mmh-1 or 57.4 mm cumulated rainfall in 24 hours is required to initiate a landslide event. Whereas, for longer duration events such as 120h, rainfall intensity of 1.93 mmh-1 or continuous rainfall of 232 mm appears to be sufficient in landslide initiation. There is a less than 5% chance of a landslide below this threshold limit. In the context of 3-day and 5-day antecedent rainfall thresholds, we found that a minimum of 130 mm in 72 h (3-day) and 210 mm in 120 h (5-day) could initiate a landslide event. We have compared our thresholds with a few global and local rainfall threshold estimates. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022: 81-94